2019
DOI: 10.1111/soc4.12698
|View full text |Cite
|
Sign up to set email alerts
|

Women's relationships with women at work: Barriers to solidarity

Abstract: Voluminous scholarship documents the wage gap, occupational segregation, sexual harassment, and other forms of gender inequality at work. Few sociological studies explore women's work relationships with other women. Our article summarizes existing research from several disciplines on women's working relationships with other women. Specifically, three themes about the conditions of work emerge that discourage women's support for other women: (a) negative stereotypes about women, (b) lack of recognition of gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 80 publications
1
32
0
1
Order By: Relevance
“…This is a gender based stereotype that is not existing in the women but it is the environment of the banks which is male dominant that gives raise to gender politics. The results are consistent with the different previous researches that the phenomena of queen bee is just a myth that has been developed by the male dominated culture (Webber & Giuffre, 2019). The findings of the research revealed that the female leaders are benefiting the female staff in different ways by inspiring and motivating their co-workers and being a role model from them to reach at top ranks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is a gender based stereotype that is not existing in the women but it is the environment of the banks which is male dominant that gives raise to gender politics. The results are consistent with the different previous researches that the phenomena of queen bee is just a myth that has been developed by the male dominated culture (Webber & Giuffre, 2019). The findings of the research revealed that the female leaders are benefiting the female staff in different ways by inspiring and motivating their co-workers and being a role model from them to reach at top ranks.…”
Section: Discussionsupporting
confidence: 91%
“…The labour market rate is 51% of total employment to population in which the ratio of female is almost 21% as compared to rate of male that is 30%, whereas the rate of female in the education and workplace is increasing with a slow trend (Statistics, 2018). Unfortunately, the female are still underrepresented in Pakistan as the number of female at top positions of leadership in the firms and politics is scarce (Webber & Giuffre, 2019). Due to the type cast of glass ceiling, the leadership is considered to be associated with male instead of female, this stereotype is resulting in reducing opportunities for female to perform the tasks of frontrunners (Baumgartner & Schneider, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A study of mentorship in the fields of accounting and engineering found that mentors, regardless of gender, provided more encouragement and efforts to improve self‐image in their mentoring to women than men, and women mentors provided more of this type of mentoring overall (Allen & Eby, 2004). Additional research found that women mentees would sometimes eschew women mentors due to beliefs that having a male mentor would provide more career benefits (Webber & Giuffre, 2019). These patterns do not always represent preference, as in many industries women in upper level positions are scarce, leaving cross‐gender mentoring as the only viable option (Ramaswami et al., 2010a).…”
Section: Mentorship Goals and Modalitiesmentioning
confidence: 99%
“…Some mentoring also happens during workshops aimed at women in the workplace (Leenders et al., 2020; Mickey, 2019b). There has also been a rise in affinity groups organized within specific industries that are especially aimed at members of groups that have historically faced workplace inequalities, including women (Webber & Giuffre, 2019). While these groups are not mentorship groups per se, they often include networking and mentorship components.…”
Section: Changes To Mentorshipmentioning
confidence: 99%
“…This culture affects the weakening of the bond of an individual with the community (Sztompka, 1996). Webber and Giuffre (2019) and Coimbra et al (2013) indicate that gender affects interpersonal relationships, including solidarity. Females show willingness to help others to a greater extent than males do (Selten and Ockenfels, 1998).…”
Section: Exchange Transactions and Socioeconomic Determinants Of Solidaritymentioning
confidence: 99%